Women on Ice : Methamphetamine Use Among Suburban Women - Boeri, Miriam (Book collections on Project MUSE., 2013)
This book explores the lives of women who use methamphetamine (ice, speed, crystal, shards) and the effects of its use on their families. In-depth interviews with women in the suburban counties of one of the largest metropolitan areas in the U.S. chronicle the details of their initiation into methamphetamine, the turning points into problematic drug use, and, for a few, their escape from lives veering out of control.